Wolf-sightings on the Canadian Arctic Islands - Miller, Frank L.; Reintjes, Frances D. (ARCTIC, 1995)
A wolf-sighting questionnaire was sent to 201 arctic field researchers from many disciplines to solicit information on observations of wolves (Canis lupus spp.) made by field parties on Canadian Arctic Islands. Usable responses were obtained for 24 of the 25 years between 1967 and 1991. Respondents reported 373 observations, involving 1203 wolf-sightings. of these, 688 wolves in 234 observations were judged to be different individuals; the remaining 515 wolf-sightings in 139 observations were believed to be repeated observations of 167 of those 688 wolves. The reported wolf-sightings were obtained from 1953 field-weeks spent on 18 of 36 Arctic Islands reported on: no wolves were seen on the other 18 islands during an additional 186 field-weeks. Airborne observers made 24% of all wolf-sightings, 266 wolves in 48 packs and 28 single wolves. Respondents reported seeing 572 different wolves in 118 separate packs and 116 single wolves. Pack sizes averaged 4.8±0.28 SE and ranged from 2 to 15 wolves. Sixty-three wolf pups were seen in 16 packs, with a mean of 3.9±2.24 SD and a range of 1-10 pups per pack. Most (81%) of the different wolves were seen on the Queen Elizabeth Islands. Respondents annually averaged 10.9 observations of wolves/100 field-weeks and saw on average 32.2 wolves/100 field-weeks/yr between 1967 and 1991. Average rates of wolf observations/100 field-weeks (28.5, 13.6 vs 5.7; p<0.005) and mean numbers of different wolves seen/100 field-weeks (92.3, 37.5 vs. 15.4; p<0.005) were markedly greater during 1967-75 and 1989-91 than in 1976-88. Relative differences in the reported rates of wolf observations on the Queen Elizabeth Islands in 1967-75, 1976-88, and 1989-91 follow the relative abundance of the wolf's major prey, Peary caribou (Rangifer tarandus pearyi) and muskoxen (Ovibos moschatus), on those islands during those periods.Key words: arctic-island wolves, Canis lupus spp., Canadian Arctic Islands, wolf-sighting questionnaire, reported wolf observations Un questionnaire portant sur ...